PERSEPSI MASYARAKAT TERHADAP AIR TERJUN ROMBO PANGA’A DI DESA ANTAN RAYAN DUSUN SUNGAI DURIAN KABUPATEN LANDAK SEBAGAI DESTINASI WISATA - Putra, Pasdo; Roslinda, Emi; Latifah, Siti (JURNAL HUTAN LESTARI, 2018)
Nature tourism is a form of recreational and tourism activity that utilizes the potential of natural resources, both in natural conditions and after cultivation, allowing tourists to obtain physical and spiritual freshness, gain knowledge and experience and foster inspiration and love for nature. Rombo Panga'a Waterfall is one of the natural attractions in Desa Antan Rayan, Dusun Sungai Durian Kecamatan Ngabang Kabupaten Landak. This research aims to determine the community perception of Rombo Panga'a waterfall as a tourist destination and how the relationship of each individual factor from the age level, education level, level of know ledge with community perception of Rombo Panga'a Waterfall. This research uses descriptive methods with interview techniques and with data collection tools, namely question naires. Data analysis was performed by means of descriptive analysis and inferential analysis, namely chi squared analysis and contingency coefficient test.The results showed that the community perception of Dusun Sungai Durian tended to be neutral towards Rombo Pang’a Waterfall as a tourist destination as many as 50 respondents (78.13%). Based on the results of the research in Dusun Sungai Durian, it tends to have a junior high school education level of 34 respondents (53.12%). Chi-square test results between independent variables and the dependent variable of all variables have a significant relationship.Keyword : Community, Nature tourism, Perception.